Addressing the social dimensions of climate change through adaptive social protection. - Ofreneo, Rosalinda Pineda (2011)
Considered a crucial development challenge of the present times, climate change increases the vulnerability of the poorest and most disadvantaged groups as in the experience of farmers, fisherfolk, indigenous peoples, women and children. With the risks associated with the phenomenon that the country is now facing, from flooding to geologic dangers, destruction of 'weather-dependent' livelihoods to health-related impacts, relevant policies and plans at the national and local governments were devised mainstreaming climate change and disaster risk reduction and management (DRRM).

The Philippines for instance has now advanced pieces of legislation to enhance, strengthen and rationalize social protection policies and programs, to further lead articulation and integration of climate change and DRRM concerns into current and future interventions. Aimed at contributing to the procecss, this 'think paper' addresses the social dimensions of climate change through espousing a rights-based, transformative, gender-responsive, participatory and sustainable approach to social protection.

This study likewise integrates the broad meanings of social protection to include economic justice, as in the rights to an adequate standard of living or in the redistributive aspect of using and owning land and water resources. It connects social protection to various conceptions of justice: gender justice, reproductive justice, environmental justice and climate justice.

Social protection to enhance adaptation and DRR benefits can be done through protective and preventive strategies of coping, as well as though promotive and transformative strategies for building adaptive capacities. The actual ability of a system to adjust (or adapt) to climate change can also be enhanced by building resilient communities through active participation of citizens, CSO and grassroots engagement, access and use of disaster information, disaster preparedness and management planning and good governance.
Keywords: Climatic changes -- Social aspects; Climate change risk management; Poor people and the environment; Emergency management